STAT3 but Not STAT5 Contributes to the Protective Effect of Electroacupuncture Against Myocardial Ischemia/Reperfusion Injury in Mice - Guo, Hui-Hui; Jing, Xin-Yue; Chen, Hui; Xu, Hou-Xi; Zhu, Bing-Mei (Frontiers in Medicine, 2021)
Electroacupuncture (EA) can help reduce infarct size and injury resulting from myocardial ischemia/reperfusion (I/R); however, the underlying molecular mechanism remains unknown. We previously reported that STAT5 plays a critical role in the cardioprotective effect of remote ischemic preconditioning (RIPC). Here, we assessed the effects of electroacupuncture pretreatment (EAP) on myocardial I/R injury in the presence and/or absence of Stat5 in mice and investigated whether EAP exerts its cardioprotective effects in a STAT5-dependent manner. Adult Stat5fl/fl and Stat5-cKO mice were exposed to EAP at Neiguan (PC6) for 7 days before the induction of I/R injury by left anterior descending (LAD) coronary artery ligation. The myocardial infarct size (IS), area at risk, and apoptotic rate of cardiomyocytes were detected. RT-qPCR and western blotting were used to measure gene and protein expression, respectively, in homogenized heart tissues. RNA-seq was used to identify candidate genes and pathways. Our results showed that EAP decreased IS and the rate of cardiomyocyte apoptosis. We further found that STAT5 was activated by EAP in Stat5fl/fl mice but not in Stat5-cKO mice, whereas the opposite was observed for STAT3. Following EAP, the levels of the antiapoptotic proteins Bcl-xL, Bcl-2, and p-AKT were increased in the presence of Stat5, while that of interleukin 10 (IL-10) was increased in both Stat5fl/fl and Stat5-cKO. The gene expression profile in heart tissues was different between Stat5fl/fl and the Stat5-cKO mice with EAP. Importantly, the top 30 DEGs under EAP in the Stat5-cKO mice were enriched in the IL-6/STAT3 signaling pathway. Our results revealed for the first time that the protective effect of EAP following myocardial I/R injury was attributable to, but not dependent on, STAT5. Additionally, we found that EAP could activate STAT3 signaling in the absence of the Stat5 gene, and could also activate antiapoptotic, survival, and anti-inflammatory signaling pathways.